iPad, iPhone and pediatric dermatology. An extra weapon or only a gadget? - Cutrone, M. (European Journal of Pediatric Dermatology, 2010)
This short review refers to iPhone and iPad, the latter on sale in Italy from a few months. Apps, namely a cross between a traditional software and a simple link to a website, are the real new event of these devices. Apps have their strength in the execution speed – all in a few seconds with a single click/touch – and in ease of downloading, installation and uninstallation. Apps are easily accessible with a touch from the appropriate icon.